Gender and sexuality in online game cultures : passionate play - Sunden, Jenny, 1973-; Sveningsson, Malin (New York : Routledge, 2012)
'How do gender and sexuality come to matter in online game cultures? Why is it important to explore'straight' versus'queer' contexts of play? And what does it mean to play together with others over time, as co-players and researchers? Gender and Sexuality in Online Game Cultures is a book about female players and their passionate encounters with the online game World of Warcraft and its player cultures. It takes seriously women's passions in games, and as such draws attention to questions of pleasure in and desire for technology. The authors use a unique approach of what they term a'twin ethnography' that develops two parallel stories. Sveningsson studies'straight' game culture, and makes explicit that which is of the norm by exploring the experiences of female gamers in a male-dominated gaming context. Sund{u296E} investigates'queer' game culture through the queer potentials of mainstream World of Warcraft culture, as well as through the case of a guild explicitly defined as LGBT.Academic research on game culture is flourishing, yet feminist accounts of gender and sexuality in games are still in the making. Drawing on feminist notions of performance, performativity and positionality, as well as the recent turn to affect and phenomenology within cultural theory, the authors develop queer, feminist studies of online player cultures in ways that are situated and embodied'--
Includes bibliographical references and index.
Keywords: Internet games -- Social aspects; Internet and women